Wind Pattern Analysis and Its Impact on Flight Safety at Fatmawati Soekarno Airport Using Wind Rose Method (2019-2023) - Agustina, Tari; Rosyid, Muhammad Ilham; Johan, Septi; Norfahmi, Siti Hairunnisa; Lizalidiawati, Lizalidiawati (Department of Physics Education, Universitas Mataram, 2025)
A study of wind patterns was conducted to minimize aircraft accidents at Fatmawati Soekarno Airport, Bengkulu City. The data was then processed using the Wrplot application to show the direction and difference in wind speed and create a wind pattern image in the form of a wind rose diagram. This study aims to analyze wind patterns and speeds at Fatmawati Soekarno Airport, Bengkulu City for a period of 5 years (2019-2023) using the Wind Rose method. Data obtained from the Meteorology, Climatology, and Geophysics Agency, Fatmawati Bengkulu Meteorology Station shows that the dominant wind direction comes from the Southeast, Northeast, and North which are influenced by seasonal changes. The results of the analysis show extreme wind speeds ranging from 2.50 - 4.70 m / s which are classified as light winds and are still safe for flight operations. With a deep understanding of this wind pattern, it is hoped that airport managers can optimize the use of runways and improve flight safety by accommodating weather conditions. The results of this study also emphasize the importance of consistent wind pattern monitoring to support risk management related to extreme weather.